Cost-effectiveness of new MDR-TB regimens: study protocol for the TB-PRACTECAL economic evaluation substudy. Issue 10 (10th October 2020) - Sweeney, Sedona; Gomez, Gabriela; Kitson, Nichola; Sinha, Animesh; Yatskevich, Natalia; Staples, Suzanne; Moodliar, Ronelle; Motlhako, Sharon; Maloma, Matshepo; Rassool, Mohammed; Ngubane, Nosipho; Ndlovu, Ella; et al.
Abstract : Introduction: Current treatment regimens for multidrug-resistant tuberculosis (MDR-TB) are long, poorly tolerated and have poor outcomes. Furthermore, the costs of treating MDR-TB are much greater than those for treating drug-susceptible TB, both for health service and patient-incurred costs. Urgent action is needed to identify short, effective, tolerable and cheaper treatments for people with both quinolone-susceptible and quinolone-resistant MDR-TB. We present the protocol for an economic evaluation (PRACTECAL-EE substudy) alongside an ongoing clinical trial (TB-PRACTECAL) aiming to assess the costs to patients and providers of new regimens, as well as their cost-effectiveness and impact on participant poverty levels. This substudy is based on data from the three countries participating in the main trial. Methods and analysis: Primary cost data will be collected from the provider and patient perspectives, following economic best practice. We will estimate the probability that new MDR-TB regimens containing bedaquiline, pretomanid and linezolid are cost-effective from a societal perspective as compared with the standard of care for MDR-TB patients in Uzbekistan, South Africa and Belarus. Analysis uses a Markov model populated with primary cost and outcome data collected at each study site. We will also estimate the impact of new regimens on prevalence of catastrophic patient costs due to TB. Ethics and dissemination: Ethical approval has been obtained from the London School of Hygiene & Tropical Medicine and Médecins Sans Frontières. Local ethical approval will be sought in each study site. The results of the economic evaluation will be shared with the country health authorities and published in a peer-reviewed journal. Trial registration number: ClinicalTrials.gov Registry (NCT04207112 ); Pre-results.